(untitled) (Research, Society and Development, 2024)
Depression is a mental disorder characterized by constant sadness, lack of interest in pleasurable activities, and in severe cases, thoughts of suicide. Omega-3 is an essential fatty acid important for human health, and there are three main types of omega-3, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) and alpha-linolenic acid (ALA). Omega-3 may play a role in mental health and its deficiency may be associated with increased depression. The objective of this article was to review the literature on the relationship between omega-3 and the prognosis of depression in adults. To this end, the PICO strategy was adopted to prepare the guiding question and the search for articles was carried out in the PubMed and CAPES Journal Portal databases. When choosing articles, the titles, abstracts and, finally, the full texts were read. 575 articles were identified, however, only 4 articles were considered eligible. Studies point to the relationship between omega 3 and depression, highlighting clinical trials that show the modest effect of n-3 polyunsaturated fatty acids, but with questionable clinical significance, and despite omega 3 showing modest effects in reducing depression, the Evidence is limited, requiring more rigorous studies to understand its real effectiveness.